Characteristics of pelargonium radula as a mercury bioindicator for safety assessment of drinking water - Phang, Ing Chia; A Majid, Noraishah (2016)
Deterioration of water quality is a worldwide issue nowadays. One of the contaminants found in surface water supplies such as lakes, rivers and reservoirs is mercury (Hg). Since Hg in drinking water poses a threat to public health, there is a need to monitor the level of Hg in drinking water for safe consumption. The routine drinking water testing is costly, laborious, and limited largely to urban areas. Plant bioindicators can be helpful in determining Hg contamination in drinking water, particularly in the rural areas. In a recent study, Pelargonium radula was found to exhibit visual morphological alteration in respond to Hg, where Hg-treated P. radula leaves changed from green to yellowish-brown, became chlorosis and wilted, in comparison to the control (A Majid and Phang, 2015). In the present study, we seek to understand the characteristics of P. radula leaves that can be used to indicate Hg in drinking water. It is found that as Hg treatments increased, Hg accumulation in the leaves of P. radula increased. However, the accumulation of Hg decreased the protein and chlorophyll contents in P. radula leaves. Additionally, the presence of Hg decreased the level of reduced glutathione, oxidized glutathione and cysteine, but increased the level of phytochelatin 2 in the leaves of P. radula. In this presentation, research and potential application of P. radula for biomonitoring Hg in drinking water will be discussed.